Marajó: espaço, sujeito e escrita - VELOSO, Ivone dos Santos (Universidade Federal do Pará, 2011)
This work thinks the romance Marajó, written by Dalcídio Jurandir as a culture good in a after-colonial perspective, in the which is questioned and re-articulated the hegemonic speeches and those ones that become the modernity.homogeneous. I consider, in this manner, to defend the idea that, to the similarity of the archipelago of Marajó, the romance homonym of Dalcídio Jurandir can say us that under the apparent homogeneity of the region it is the ambivalent and the heterogeneous, and that this narrative redefine, therefore, the symbolic process and the social imaginary on the Amazonian that, traditionally, have constituted the image of this region. For in such a way, I demonstrate how is forged a new cultural sign from the representation of a space that oscillates between document and fiction, as well as from the representation of a citizen in bordering and ambivalent condition and of a writing that makes itself fragmentary and double. The theoretical frecital of this study consists, over all, in backgrounds about the construction of established represent a nation and create a cultural identity, mainly, by Timothi Brennan, Homi Bhabha and Stuart Hall, as well as, in the idea of dissimulation and supplement inferred of the studies of Barthes and Jacques Derrida; in the contributions of Deleuze and Guatarri, Donaldo Schuller, Finazzi-Agro,Garcia Canclini, Costa Lima, Angel Rama, amongst other, to think the condition of the citizen and the construction of the space about the Dalcídio”s narrative, and, still, in the analytical contributions of researchers of the Dalcídio‟s work as Assmar, Vicente Salles, Marli Tereza Furtado, Castilo,dentre many other.